Enlightenment versus Counter-Enlightenment: Isaiah Berlin's account on the sciences and the humanities - Silva, Elisabete Mendes (2015)
Isaiah Berlin, one of the most renowned liberal intellectuals of the twentieth century, dedicated his life to the study of ideas, demonstrating how their power influenced and changed world history. A defender of value pluralism, Berlin was against a priori, absolute truths and axiomatic premises safeguarded by the empiricist philosophers of the seventeenth and eighteenth centuries. This being said, in this paper I intend to give account of Isaiah Berlin’s ideas in regards to the divorce between the sciences and the humanities, which started with the seventeenth and eighteenth centuries’ champions of reason whose sole purpose was ‘to bring everything before the bar of reason’. Berlin gives us a very acute and precise lesson on how this growing tension and great divorce became clear since the seventeenth century up to the present day. An admirer of the Counter-Enlightenment philosophers – Vico, Herder and Hamann – Berlin denies the existence of a perfect world so much sought by the Enlightenment philosophes. This dichotomy will therefore be highlighted as a means to present Berlin’s position, that of agonistic liberalism and value-pluralism, always struggling for the importance of both the sciences and the humanities.